1998
DOI: 10.1021/bi981143p
|View full text |Cite
|
Sign up to set email alerts
|

FTIR and UV Spectroscopy of Parallel-Stranded DNAs with Mixed A•T/G•C Sequences and Their A•T/I•C Analogues

Abstract: The infrared spectra of parallel-stranded (ps) hairpin duplexes with mixed A*T/G*C composition and either isolated or sequential G*C pairs were studied in comparison with antiparallel-stranded (aps) duplexes and a corresponding set of molecules with hypoxanthine as a G base analogue lacking the exocyclic amino group. The ps duplexes showed the characteristic bands for the C2=O2 and C4=O4 stretching vibrations of thymine residues in trans-Watson-Crick A*T pairing at 1683 and 1668 cm-1. The latter band was super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…PD173074 (Sigma‐Aldrich, Dorset, UK), a potent, cell permeable and ATP competitive inhibitor of FGFR (Mohammadi et al , ) was dissolved in DMSO (stock: 20 mM) to be used at a 2 μM final concentration. Equivalent volumes of vehicle (DMSO) served as control.…”
Section: Methodsmentioning
confidence: 99%
“…PD173074 (Sigma‐Aldrich, Dorset, UK), a potent, cell permeable and ATP competitive inhibitor of FGFR (Mohammadi et al , ) was dissolved in DMSO (stock: 20 mM) to be used at a 2 μM final concentration. Equivalent volumes of vehicle (DMSO) served as control.…”
Section: Methodsmentioning
confidence: 99%
“…These results are consistent with experiments indicating a reduced stability of the W:W trans geometry for the G:C pair. For example, it has been shown that the introduction of G:C W:W trans base pairs in all A-T parallel strand DNA duplexes, characterized by W:W trans base pairs (31,32), significantly reduces the duplex thermodynamic stability, both for base stacking and hydrogen bonding contributions (33,34). …”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies on parallel strand DNA (psDNA) duplexes, characterized by RWC base pairs (Pattabiraman 1986;Mohammadi et al 1998), have shown that, whereas the all A-T psDNA duplexes are quite stable, the introduction of G-C base pairs significantly reduces the psDNA duplex thermodynamic stability, both for base stacking and hydrogen bonding contributions (Rippe et al 1990;Rentzeperis et al 1992). Moreover, theoretical studies have shown that repulsive amino-amino and carbonyl-carbonyl contacts make the RWC arrangement unfavorable for an isolated G-C pair in the gas phase (Zhanpeisov et al 1998).…”
Section: Introductionmentioning
confidence: 99%